2005
DOI: 10.1111/j.1365-313x.2005.02480.x
|View full text |Cite
|
Sign up to set email alerts
|

EgMYB2, a new transcriptional activator from Eucalyptus xylem, regulates secondary cell wall formation and lignin biosynthesis

Abstract: SummaryEgMYB2, a member of a new subgroup of the R2R3 MYB family of transcription factors, was cloned from a library consisting of RNA from differentiating Eucalyptus xylem. EgMYB2 maps to a unique locus on the Eucalyptus grandis linkage map and co-localizes with a quantitative trait locus (QTL) for lignin content. Recombinant EgMYB2 protein was able to bind specifically the cis-regulatory regions of the promoters of two lignin biosynthetic genes, cinnamoyl-coenzyme A reductase (CCR) and cinnamyl alcohol dehyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
266
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 321 publications
(291 citation statements)
references
References 45 publications
9
266
0
1
Order By: Relevance
“…Transcriptional switches for programs involving different cell wall gene networks involving a switch from primary to secondary wall include both NAC-domain (10) and Myb transcription factors (11). The lack of secondary wall formation but not cellular specification when these and other NAC-domain containing proteins are repressed and the induction of ectopic secondary walls in overexpressing lines provide strong evidence for control of cell wall gene networks (10).…”
Section: Discussionmentioning
confidence: 96%
“…Transcriptional switches for programs involving different cell wall gene networks involving a switch from primary to secondary wall include both NAC-domain (10) and Myb transcription factors (11). The lack of secondary wall formation but not cellular specification when these and other NAC-domain containing proteins are repressed and the induction of ectopic secondary walls in overexpressing lines provide strong evidence for control of cell wall gene networks (10).…”
Section: Discussionmentioning
confidence: 96%
“…Even though array-based studies are useful for discovering candidate genes, functional studies can confirm the role of a gene in controlling a trait. Goicoechea et al (2005) characterized the role of EgMYB2, a transcriptional activator identified from differentiating xylem from Eucalyptus. Using proteinbinding analyses, they showed that EgMYB2 specifically binds to the promoters of CCR and CAD, the two terminal genes in the lignin biosynthetic pathway, and regulates their expression.…”
Section: Gene Discovery and Association Geneticsmentioning
confidence: 99%
“…Several MYB proteins may be involved in secondary metabolism [7][8][9]. AtMYB0/GL1 is required for leaf trichome differentiation [10].…”
Section: Introductionmentioning
confidence: 99%